Peningkatan Keterlibatan Stakeholder Dalam Perumusan Peraturan Nagari Layak Anak - Hidayatul Fajri; Artha Dini Akmal; Boni Saputra; Karjuni Dt. Maani; Iip Permana; Nila Wahyuni; Rizki Syafril (Universitas Lancang Kuning, 2020)
Nagari Situmbuk and Nagari Tabek Patah, our activity partners, do not yet have regulations governing the protection of public spaces that are suitable for children. Whereas Law No. 23/2002 requires every city/regency and village to have a child-friendly environment, also Law_No._35 of 2014 concerning_child_protection demands the same thing. The urgency was also emphasized by the issuance of the_Regulation_of_the_Minister_of Women_Empowerment and Child_Protection of the Republic of Indonesia No 13 of 2010 Technical Guidelines for Eligible Districts / Cities in Children / Villages and Regional Regulation of Tanah Datar District No. 6 of 2018 concerning Implementation of Child Protection. Therefore, the existence of the Nagari Rule on Child-Friendly Nagari as important as participatory and collaborative policy formulation capabilities is held at the nagari level. It was marked by the involvement of stakeholders aiming that the policy would get full commitment from all parties. This activity is carried out using a participatory and collaborative training approach method. The results of devotion show that the involvement of stakeholders is still low in the formulation of policies in both of our partner villages. This is caused by 1) their lack of knowledge about children's rights and 2) communication, interaction, and exchange of information among stakeholders that is low so that it fails to form a policy network..